PENINGKATAN MOTIVASI BELAJAR ANAK MELALUI METODE DISKUSI INTERAKTIF - Taufiqul Firdaus; Assyafa'ul Basith; Andriko Sandria (LPPM Universitas Al Muslim, 2023)
Education is an important sector that helps children's future to be brighter. The Covid-19 pandemic which has subsided makes educational activities run normally. Changing online activities to offline makes children need to adjust again. In addition, not every child can respond quickly in understanding the material presented at school. Of course, interactive learning activities are needed and can help children. Sebelas Maret University (UNS) Real Work Lecture (KKN) students held community service activities in the form of study assistance for Pendem Village Elementary School children from class I to class VI. The program held was titled Pendem Learning, which utilized interactive discussion methods. The Pendem Learning Program run well and smoothly and was able to increase children's motivation in carrying out learning. Through this program, it is hoped that the youth or Karang Taruna of Pendem Village can continue or improve the quality of learning at Pendem Learning, so that in the future they can produce better generations of Pendem Village in terms of the quality of their human resources.